Physical Activity for Executive Function and Activities of Daily Living in AD Patients: A Systematic Review and Meta-Analysis - Zhu, Lin; Li, Long; Wang, Lin; Jin, Xiaohu; Zhang, Huajiang (Frontiers in Psychology, 2020)
Objectives: The aim of the present study was to systematically analyze the effects of physical activity for AD patients with executive function,working memory，cognitive flexibility and ADL and provide scientific evidence-based exercise prescription. Methods: both Chinese and English databases(PubMed, Web of Science, the Cochrane Library, EMBASE , VIP Database for Chinese Technical Periodicals, China National Knowledge Infrastructure, Wanfang )were used as sources of data to search randomized controlled trials (RCT) relating to physical activity in AD patients with executive function, working memory,cognitive flexibility and ADL that were published between January 1980 to December 2019.16 eligible RCT studies were finally used for meta-analysis. Results: physical activity had significant benefits on AD patients with executive function (SMD= 0.42, 95% CI 0.22 to 0.62, p=0.047, I2=44.8%) and ADL (SMD= 0.68, 95% CI 0.19 to 1.16, p=0.000, I2=86.4%). Sub-group analysis indicated that, for executive function, more than 60 min per session for 16 weeks of moderate-to-high intensity physical activity had a greater effect on patients with AD patients. Meanwhile,for working memory and cognitive flexibility,1-2 times a week,3-4 times a week,and 60-90 minutes of moderate-intensity physical activity was more effective. For ADL, 3-4 times a week, 30-90 min each time,60-79% HR of physical activity had a higher effect on patients with AD. Conclusions: Physical activity were found to have significant improvements in executive function,working memory,cognitive flexibility and ADL in patients with AD , and can be used as an effective method for clinical exercise intervention in AD patients. At the same time, more objective, scientific, and effective randomized controlled trials are needed to prove this conclusion.